THE EFFECTIVENESS OF USING PBL METHODS ON STUDENTS WRITING ABILITY IN SENIOR HIGH SCHOOL - Auliya, Silma Nur Rifa; Ruswandi, Riki; Gaffar, Muhammad Andriana (Premise: Journal of English Education and Applied Linguistics, 2025)
The Project-Based Learning (PBL) model is still rarely used in learning to write recount texts, even though it has significant potential to improve students' writing skills. Therefore, this research focuses on improving students' recount text writing skills using Project-Based Learning (PBL) models. It aims to see how effectively the PBL models can improve students' ability to write Recount Text for SMA Negeri 21 Bandung tenth-grade students. This research uses a quantitative approach with a survey design. The data collection technique for this research uses a questionnaire with the application of a five-point Likert scale with descriptive statistics analysis. Based on the survey, the findings of this research show that using the PBL models can effectively improve students' ability to write recount text. The survey results showed an average score of 3.74, with 7.4% of respondents strongly agreeing, 61.1% agreeing, 29.6% neutral, and 1.9% disagreeing. In addition, student perceptions state that this model helps learning and increases Motivation and engagement. The survey revealed that students felt more motivated to write Recount Text after participating in PBL. The data showed that 5.6% of respondents strongly agreed, 55.6% agreed, and 37.0%  respondents were neutral. The study also found that PBL models involved students more in learning activities than other models, with an average score of 3.65. The implications of this research show that PBL improves students' ability to write recount texts by involving them in projects, providing constructive feedback, and increasing activity, Motivation, and creativity.